Highly Enhanced Enzymatic Activity of Mn-Induced Carbon Dots and Their Application as Colorimetric Sensor Probes - Ahyun Lee (MDPI AG, 2021)
Nanomaterial-based enzyme mimetics (nanozymes) have attracted significant interest because of their lower cost and higher stability compared to natural enzymes. In this study, we focused on improving the enzymatic properties of metal induced N-doped carbon dots (N-CDs), which are nanozymes of interest, and their applications for sensory systems. For this purpose, Mn(acetate)2 was introduced during the synthetic step of N-doped carbon dots, and its influence on the enzymatic properties of Mn-induced N-CDs (Mn:N-CDs) was investigated. Their chemical structure was analyzed through infrared spectroscopy and X-ray photoelectron spectrometry; the results suggest that Mn ions lead to the variation in the population of chemical bonding in Mn:N-CDs, whereas these ions were not incorporated into N-CD frameworks. This structural change improved the enzymatic properties of Mn:N-CDs with respect to those of N-CDs when the color change of a 3,3′,5,5′-tetramethylbenzidine/H2O2 solution was examined in the presence of Mn:N-CDs and N-CDs. Based on this enhanced enzymatic property, a simple colorimetric system with Mn:N-CDs was used for the detection of γ-aminobutyric acid, which is an indicator of brain-related disease. Therefore, we believe that Mn:N-CDs will be an excellent enzymatic probe for the colorimetric sensor system.